Cuerpo y afecto en Noches de adrenalina (1981) de Carmen Ollé - Fernández Cozman, Camilo Rubén (2021)
This article presents an analysis of Nights of Adrenaline by the Peruvian poet Carmen Ollé based on the notion of performatic body and affect. The poetic subject questions the imposed roles to women by androcentric society and manifests the migratory shift from the periphery (Lima) to Europe (the center). Likewise, Ollé proposes body liberation based on Anti-Psychiatry and Radical Psychiatry theorists as an implicit criticism to Psychiatry, Psychoanalysis and religion. For this reason, she postulates the emergence of a queer desire.